The Effect of Halal Certification on Logistic Performance and Financial Performance : Case Study: Processed Meat and Cowhide SMEs in Surakarta - Santosa, Calvin William; Fahma, Fakhrina; Damayanti, Retno Wulan (Institute of Research and Community Outreach - Petra Christian University, 2022)
Amid increasingly fierce competition in the food business, halal certification is a source of excellence. Halal certification is now a step businesses can take to increase their successful business performance. This study aims to provide business actors with a deeper understanding of the impact of halal certification on company performance by analyzing the effect of halal certification on logistic performance and financial performance in small and medium-sized enterprises (SMEs) based on processed meat and cowhide in Surakarta. This study is based on a purposive sampling survey of SMEs producing processed meat and cowhide in Surakarta that has obtained halal certification. The PLS-SEM method was used to process the data. This research shows that halal certification has a good and significant impact on the logistical and financial performance of SMEs producing processed meat and cowhide in Surakarta. This founding indicates that halal certification has an impact and may be considered by business actors who have yet to go through the process.